Estimation of two species of urban plants for airborne particulates deposition - Mohd Azam, Nur Dina Shazani (2013)
Urban vegetation plays an important role in amelioration of city environment. Urban vegetation entraps air pollutants on the surface of the leaves. This could reduce longterm threat to human health, microclimate and ecosystems as well. However, this benefit is not fully explored in Malaysia and the studies are very scarce. The objectives of this study were to estimate the amount of airborne pollutants deposited onto the leaves of two selected urban plants and identify the elements present according to the response-relationship of several factors. Samples of particulates were collected on the leaves surfaces of Acalypha siamensis at the Country Heights Kajang and Ficus microcarpa at the Jalan Hang Tuah, Kuala Lumpur by using Cyclopore Track Etched Membrane Filter. Samples were obtained at two levels of plants’ canopy for three different periods of exposure (24, 48 and 72 hours). Samples were then screened using SEM-EDX and EDXRF Spectroscopy. The deposited particulates were mostly in an agglomeration form and 26 elements of airborne pollutants were detected using the EDXRF. PM (235469.317±22536.715), Al (3171.923±906.808) and Si (308.948±64.776) were found to be the highest percentage in Jalan Hang Tuah, Kuala Lumpur whereas PM (159461.704±13523.958), Al (2794.384±633.483) and Mg (242.701±8.728) were the highest quantities found in Country Heights Kajang. However, most of the elements’ concentration was not greatly influenced by the increasing or decreasing of the hour of exposure. The results showed Na, Mg, Si, Zn, As, W and Al were highly significant at Country Heights Kajang for 24, 48 and 72 hours, whereas at Jalan Hang Tuah, Na, Mg, Si, K, Co, Ba and particulate matter were highly significant indicating that concentration varied with times. The findings showed that the elements’ concentration was greatly influenced by the meteorological parameters. Ca increases with the increased of wind speed at Jalan Hang Tuah, whereas at Country Heights Kajang, Mg was correlated to mean temperature and rainfall; K, Cu, Th and PM were correlated to wind speed; Rb and W were correlated to minimum temperature while Mn, W and PM were highly correlated to relative humidity. However, the elements’ concentration on the upper and lower parts of the canopy was not statistically different at both sites. The results also showed the elements with their possible sources; Country Heights Kajang: K and Ca (7.898%) were originated from construction while Sc, Ni, Cr, Ti and S (17.592%) were mainly emitted from sediments or road dust along Jalan Hang Tuah. The results showed 17 elements were highly enriched at Country Heights Kajang whereas 12 elements were significant to extremely enriched at Jalan Hang Tuah. However, further investigations need to carry out holistically by considering other possible factors which may influence the dispersion of airborne pollutants.